Correlation between Clinical Outcomes and Baseline CT and CT Angiographic Findings in the SWIFT PRIME Trial - Jadhav, A.P. (AJNR Am J Neuroradiol, 2017)
BACKGROUND AND PURPOSE: Patient selection for endovascular therapy remains a great challenge in clinic practice. We sought to determine the effect of baseline CT and angiography on outcomes in the Solitaire With the Intention for Thrombectomy as Primary Endovascular Treatment for Acute Ischemic Stroke (SWIFT PRIME) trial and to identify patients who would benefit from endovascular stroke therapy. MATERIALS AND METHODS: The primary end point was a 90-day modified Rankin Scale score of 0–2. Subgroup and classification and regression tree analysis was performed on baseline ASPECTS, site of occlusion, clot length, collateral status, and onset-to-treatment time. RESULTS: Smaller baseline infarct (n = 145) (ASPECTS 8–10) was associated with better outcomes in patients treated with thrombectomy versus IV tPA alone (66% versus 41%; rate ratio, 1.62) compared with patients with larger baseline infarcts (n = 44) (ASPECTS 6–7) (42% versus 21%; rate ratio, 1.98). The benefit of thrombectomy over IV tPA alone did not differ significantly by ASPECTS. Stratification by occlusion location also showed benefit with thrombectomy across all groups. Improved outcomes after thrombectomy occurred in patients with clot lengths of ≥8 mm (71% versus 43%; rate ratio, 1.67). Outcomes stratified by collateral status had a benefit with thrombectomy across all groups: none–fair collaterals (33% versus 0%), good collaterals (58% versus 44%), and excellent collaterals (82% versus 28%). Using a 3-level classification and regression tree analysis, we observed optimal outcomes in patients with favorable baseline ASPECTS, complete/near-complete recanalization (TICI 2b/3), and early treatment (mean mRS, 1.35 versus 3.73), while univariate and multivariate logistic regression showed significantly better results in patients with higher ASPECTS. CONCLUSIONS: While benefit was seen with endovascular therapy across multiple subgroups, the greatest response was observed in patients with a small baseline core infarct, excellent collaterals, and early treatment.